Peran Ekstrakurikuler Retorika Dakwah dalam Meningkatkan Kemampuan Public Speaking Santri di Pesantren Persatuan Islam 67 Benda Kota Tasikmalaya - Inka Kaniati Lathifah; Chairiawaty (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. Rhetoric plays an important role in da'wah, which is an effort to convey the message of Islam to the community. to train students' public speaking skills, Islamic Unity Boarding School 67 Benda Tasikmalaya City holds extracurricular da'wah rhetoric. This study aims to determine the Role of Extracurricular Rhetoric of Da'wah on Students' Public Speaking Skills at Islamic Unity Boarding School 67 Benda Tasikmalaya City. This research uses a qualitative method using Soerjono Soekanto's role theory. The results showed that extracurricular preaching rhetoric plays an active role in improving students' public speaking skills. The inhibiting factor experienced by students in participating in extracurricular preaching rhetoric is a lack of self-confidence. Extracurricular preaching rhetoric plays an active role in the students' public speaking skills. Students who take part in this program experience an increase in several aspects of public speaking skills, including mastery of speaking techniques, self-confidence, and the ability to convey messages clearly and persuasively. Abstrak. Retorika memegang peranan penting dalam dakwah, yang merupakan upaya menyampaikan pesan Islam kepada masyarakat. untuk melatih kemampuan public speaking santri, Pesantren Persatuan Islam 67 Benda Kota tasikmalaya mengadakan ekstrakurikuler retorika dakwah. Penelitian ini bertujuan untuk menetahui Peran Ekstrakurikuler Retorika Dakwah terhadap Kemampuan Public Speaking Santri di Pesantren Persatuan Islam 67 Benda Kota Tasikmalaya. Penelitian ini menggunakan metode kualitatif dengan menggunakan teori peran Soerjono Soekanto. Hasil penelitian menunjukkan bahwa ekstrakurikuler retorika dakwah berperan aktif dalam meningkatkan kemampuan public speaking santri. Faktor penghambat yang dialami santri dalam mengikuti ekstrakurikuler retorika dakwah adalah kurangnya kepercayaan diri. Ekstrakurikuler retorika dakwah berperan aktif terhadap kemampuan public speaking santri. Santri yang mengikuti program ini mengalami peningkatan dalam beberapa aspek kemampuan berbicara di depan umum, termasuk penguasaan teknik berbicara, kepercayaan diri, serta kemampuan menyampaikan pesan dengan jelas dan persuasif.